2019
DOI: 10.1097/nnr.0000000000000352
|View full text |Cite
|
Sign up to set email alerts
|

A Multigroup Analysis of the Effect of Cognitive Appraisal on Nurses' Psychological Distress

Abstract: The study was conducted in accordance with the internal guidelines of the Research Centre of Psychology, from the University of Minho, being in conformity with both the national and European regulations, regarding research with human participants and the management of personal data. The study was exempt from institutional review board approval.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Lazarus and Folkman (1984a, 1984b, 1987) developed the cognitive appraisal theory of stress in explaining the underlying process of stress perception. The theory has been widely applied to stress studies in different populations, for example, education practitioners (Gomes et al., 2013; McCarthy et al., 2016), athletes (Didymus & Fletcher, 2017; Puente‐Diaz & Anshel, 2005), nurses (Simães et al., 2019), cancer patients (Chen et al., 2018; Hamama‐Raz & Solomon, 2006), and stress management interventions (Junker et al., 2020). Its major theoretical contribution is that subjective interpretations of an event, which involve cognitive appraisals of the perceivers, determine their perception of stress.…”
Section: Introductionmentioning
confidence: 99%
“…Lazarus and Folkman (1984a, 1984b, 1987) developed the cognitive appraisal theory of stress in explaining the underlying process of stress perception. The theory has been widely applied to stress studies in different populations, for example, education practitioners (Gomes et al., 2013; McCarthy et al., 2016), athletes (Didymus & Fletcher, 2017; Puente‐Diaz & Anshel, 2005), nurses (Simães et al., 2019), cancer patients (Chen et al., 2018; Hamama‐Raz & Solomon, 2006), and stress management interventions (Junker et al., 2020). Its major theoretical contribution is that subjective interpretations of an event, which involve cognitive appraisals of the perceivers, determine their perception of stress.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, subjective appraisal has been found to significantly relate to employees' coping strategies, affective and behavioral responses, as well as to employees' working attitudes and performance [5,7]. In addition, recent research has shown that challenge and threat perceptions relate to psychological distress, becoming central variables as regards to the prediction of mental health [14]. Finally, and in line with the TTS, previous studies have shown that employees might appraise job demands simultaneously as having the potential for harm and gain, and that these appraisals may fluctuate from day to day [5,7].…”
Section: Examining Subjective Appraisal Of Job Demandsmentioning
confidence: 99%
“…Thus, it is important to gather knowledge about these phenomena in order to contribute for the development of coping mechanisms and the creation of healthy work environments where employees can feel valued and satisfied. Curiously, there are much more evidence about the stress and burnout experience in health activities, such as nurses and even doctors (Gomes et al, 2009;Gomes, 2014b;Silva & Gomes, 2009;Simães et al, 2019), but less evidence exists with social workers, even though their work environment presents several risk factors for the development of stress and burnout (Moreno et al, 2014;Sequeira, 2017), as is the case of overwork with little monetary compensation, a pressure to perform tasks, the absence of support resources, and the need to assume multiple responsibilities (Calitz et al, 2014).…”
Section: Stress éValuation Cognitive Et éPuisement Professionnel Chez...mentioning
confidence: 99%